The link between corporate social performance and financial performance: Evidence from Indonesian companies - Fauzi, Hasan; Mahoney, Lois S.; Abdul Rahman, Azhar (Indonesian Center for Social and Environmental Research and Development, 2007)
This study examines the relationship of corporate social performance (CSP) to corporate financial performance (CFP) to determine if CSP is related to firm performance. Additionally, it examines whether firm size or industry affects the relationships between CSR and CSP. This study advances the literature as it examines this relationship for companies in a developing country, Indonesia, along with examining the impact of moderating variables on this relationship. Two models were developed: the first model was derived using slack resource theory and the second model was developed using the good management theory. Through the examination of 383 firms, the result of the study failed to find a significant relationship between CSP and CFP in either model. Further analysis, using the slack resource theory, did find that company size had a significant positive moderating effect on the relationship between CSP and CFP.